Corporate social responsibility and stock price volatility : evidence from Malaysian banking sector / Nur Aliah Aisyah Nor Sazli - Nor Sazli, Nur Aliah Aisyah (2021)
Despite growing recognition of the importance of Corporate Social Responsibility (CSR) on a global scale, there have been limited studies on these topics from the Malaysian banking sector perspectives. Therefore, the study aims at examining the relationship between stock price and Corporate Social Responsibility (CSR) of selected banks in Malaysia from 2010 to 2019 using the static panel regressions namely POLS, FEM and REM. The findings suggest that FE models are generally more favourable than POLS and REM. CSR has a negative and significant association with Malaysian banks' stock price volatility (SPV), and so do the dividend yield and bank size while tax exhibits a positive relationship. Future studies may consider the effects of CSR on business risk in the contexts of Islamic and conventional banks.